2017
DOI: 10.1007/s00415-017-8512-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with quality of life among people with drug-resistant epilepsy

Abstract: Quality of Life (QoL) is the preferred outcome in non-pharmacological trials, but there is little UK population evidence of QoL in epilepsy. In advance of evaluating an epilepsy self-management course we aimed to describe, among UK participants, what clinical and psycho-social characteristics are associated with QoL. We recruited 404 adults attending specialist clinics, with at least two seizures in the prior year and measured their self-reported seizure frequency, co-morbidity, psychological distress, social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 42 publications
(79 reference statements)
10
54
2
1
Order By: Relevance
“…Psychological symptoms were reported frequently, with 54% reporting current anxiety symptoms and 28% reporting current depression symptoms at borderline or case‐level. There was much variation in QoL scores from 24.5 to 97.6, and it was most strongly associated with presence or absence of psychological symptoms . This has also been reported elsewhere …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Psychological symptoms were reported frequently, with 54% reporting current anxiety symptoms and 28% reporting current depression symptoms at borderline or case‐level. There was much variation in QoL scores from 24.5 to 97.6, and it was most strongly associated with presence or absence of psychological symptoms . This has also been reported elsewhere …”
Section: Discussionsupporting
confidence: 78%
“…However, using our baseline data, we found that seizure frequency was only weakly associated with QoL. We found psychological distress was most associated with lower QoL in our group of PWE . There is no literature evidence to suggest that a solely educational intervention has ever changed QoL after 12 months in people with epilepsy .…”
Section: Discussionmentioning
confidence: 49%
“…The relevance of depressive symptom severity to the quality of life and other outcomes in people with epilepsy is substantial, and for this reason, the Managing Epilepsy Well Network has prioritized a focus on mental health comorbidity . A study of people with poorly controlled epilepsy found that in the order of large to small magnitude, depression, low self‐mastery, anxiety, stigma, medical and psychiatric comorbidity, poor medication adherence, and more frequent seizures were associated with worse quality of life . A previous report by these investigators found that NHEs confined to ER visits and hospitalizations were more common in people with epilepsy and comorbid mental illness versus in people with epilepsy who did not have mental health comorbidity …”
Section: Discussionmentioning
confidence: 99%
“…Even a single seizure is associated with reduced HRQOL . Several factors contribute to poor HRQOL, especially when seizure freedom cannot be achieved, including medication side effects, the number of antiepileptic drugs (AEDs), psychological symptoms (eg, depression), and psychosocial difficulties (eg, unemployment) …”
Section: Introductionmentioning
confidence: 99%